Optimization of the dosage regimen of zoledronic acid with a kinetic-pharmacodynamic model and exposure-response analysis - Wang, Huan; Liu, Qi; Jiang, Muhan; Song, Chunli; Liu, Dongyang (Frontiers in Pharmacology, 2023)
Purpose: In order to support the dose optimization of zoledronic acid, the kinetic-pharmacodynamic model and exposure-response analysis were used to describe the changes in bone mineral density in different doses of zoledronic acid and establish the relationship between dose and acute phase reaction .Methods: Data were extracted from literature in accessible public databases. The kineticpharmacodynamic model was developed based on the above data using the NONMEM package to estimate parameters describing the relationship between the dose of zoledronic acid and bone mineral density. Exposure-response analysis was developed to establish the relationship between dose and acute phase reaction. Model evaluation was performed using goodness-of-fit, coefficient of variation (CV%). And sensitivity analyses were performed to assess the necessity of related parameters. Then the established model was used to simulate the changes of bone mineral density under different administration regimens, and the literature data was verified.Results: The kinetic-pharmacodynamic model successfully described zoledronic acid dose and change of bone mineral density in osteoporosis patients, with coefficient of variation of most less than 71.5%. The exposure-response analysis showed the incidence of acute phase reaction is dosedependent. The bone mineral density was simulated based on the developed kineticpharmacodynamic model. And the simulated change of bone mineral density and the incidence of acute phase reaction could be helpful to propose a dosage regimen.Conclusion: Overall, the kinetic-pharmacodynamic model described changes of bone mineral density in different doses of zoledronic acid in vivo. And, the model and the exposure-response analysis also showed to provide the assessment of dose-response relationship for zoledronic acid.